Consultation audio-recording reduces long-term decision regret after prostate cancer treatment: A non-randomised comparative cohort study. Issue 6 (December 2016) - Good, Daniel W.; Delaney, Harry; Laird, Alexander; Hacking, Belinda; Stewart, Grant D.; McNeill, S. Alan
Abstract: Introduction: The life expectancy of prostate patients is long and patients will spend many years carrying the burdens & benefits of the treatment decisions they have made, therefore, it is vital that decisions on treatments are shared between patient and physician. The objective was to determine if consultation audio-recording improves quality of life, reduces regret or improves patient satisfaction in comparison to standard counselling. Patients and methods: In 2012 we initiated consultation audio-recordings, where patients are given a CD of their consultation to keep and replay at home. We conducted a prospective non-randomised study of patient satisfaction, quality of life (QOL) and decision regret at 12 months follow-up using posted validated questionnaires for the audio-recording (AR) patients and a control cohort. Qualitative and thematic analyses were used. Results: Forty of 59 patients in the AR group, and 27 of 45 patients in the control group returned the questionnaires. Patient demographics were similar in both groups with no statistically significant differences between the two groups. Decision regret was lower in the audio-recording group (11/100) vs control group (19/100) ( p  = 0.04). The risk ratio for not having any long-term decision regret was 5.539 (CI 1.643–18.674), with NNT to prevent regret being 4. Regression analysis showed that receiving audio-recording was strongest predictor for absence of regret even greater than potency and incontinence. Conclusion: The study has shown that audio-recording clinic consultation reduces long-term decision regret, increases patient information recall, understanding and confidence in their decision. There is great potential for further expansion of this low-cost intervention.